Graves’ disease and systemic lupus erythematosus: a Mendelian randomization study - Xian, Wei; Liu, Boyuan; Li, Jinjian; Yang, Yuxin; Hong, Shubin; Xiao, Haipeng; Wu, Dide; Li, Yanbing (Frontiers in immunology, 2024)
Previous observational studies have established a correlation between Graves' disease(GD) and systemic lupus erythematosus(SLE). However, whether a causal relationship exists between these two diseases remains unknown.We utilized Mendelian randomization to infer the causal association between GD and SLE. This study employed GWAS summary statistics of GD and SLE in individuals of Asian descent. The random effect inverse variance weighted (IVW) method was utilized to aggregate the causal effect estimates of all SNPs. Cochran's Q values were computed to evaluate the heterogeneity among instrumental variables. Sensitivity analyses such as MR-Egger method, median weighting method, leave-one-out method, and MR-PRESSO method were used to test whether there was horizontal pleiotropy of instrumental variables. Our study found genetically predicted GD may increase risk of SLE (OR=1.17, 95% CI 0.99-1.40, p=0.069). Additionally, genetically predicted SLE elevated the risk of developing GD by 15% (OR=1.15, 95% CI 1.05-1.27, p= 0.004). After correcting for possible horizontal pleiotropy by excluding outlier SNPs, the results suggested that GD increased the risk of SLE (OR=1.27, 95% CI 1.09-1.48, =0.018), while SLE also increased the risk of developing GD (OR=1.13, 95% CI 1.05-1.22, =0.003). The findings of the study indicate that there may be a correlation between GD and SLE, with each potentially increasing the risk of the other. These results have important implications for the screening and treatment of patients with co-morbidities in clinical settings, as well as for further research into the molecular mechanisms underlying the relationship between GD and SLE.